Hubungan Dukungan Sosial Keluarga Dengan Tingkat Kecemasan Pasien Covid-19 Yang Menjalani Isolasi Di RSUD Abdul Manan Simatupang Kisaran Tahun 2021 - Paskah Rina Situmorang, Suryani Ginting (CV. PUSDIKRA MITRA JAYA, 2022)
Coronavirus is a group of viruses that cause disease in humans and animals. This Coronavirus disease if infected in humans can cause infectious diseases of the respiratory tract, with symptoms ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). For this reason, it is necessary to have support from the family to reduce the level of anxiety in patients undergoing isolation. This study aims to identify how the relationship between family social support and the anxiety level of COVID-19 patients is by using a descriptive correlation with a Cross Sectional study design. The sample in this study was patients who experienced COVID-19 as many as 31 respondents at the Abdul Manan Simatupang Hospital, Kisaran. The sampling technique uses non-probability sampling, namely purposive sampling. The instrument is a family social support questionnaire and the anxiety level of Covid-19 patients undergoing isolation. The results showed that there was a relationship between family social support (Emotional Support, Appreciation Support, Instrumental Support, and Informative Support) with the anxiety level of Covid-19 patients where p < 0.05 and the relationship was strong, this was indicated by the value of r = 0.656. It can be concluded that social support from family is very helpful to reduce anxiety in patients undergoing isolation. For this reason, it is hoped that families will continue to provide family social support for patients undergoing isolation.